Retrospective assessment of the frequency of cancer in the population of kidney transplant recipients - the experience of two transplant centers - Komorowska-Jagielska, Karolina; Dębska-Ślizień, Alicja; Kolonko, Aureliusz; Heleniak, Zbigniew; Ruszkowski, Jakub; Czarnacka, Kamila; Imko-Walczuk, Beata; Biedunkiewicz, Bogdan; Bułło-Piontecka, Barbara; Bzoma, Beata; Chamienia, Andrzej; Gołębiewska, Justyna; et al. (Frontiers in Oncology, 2025)
IntroductionCancer is one of the main causes of death among kidney recipients. The risk of cancer in kidney transplant recipients (KTRs) is 2–3 times higher as compared to the general population.AimRetrospective assessment of the occurrence of cancer in the population of KTRs – based on data from two transplant centers.MaterialThe study included a total of 246 KTRs, transplanted between 1980 and 2021, who were diagnosed with malignancy (the study did not include patients whose only cancer was non-melanoma skin cancer; NMSC).Results261 malignant tumors were diagnosed in 246 KTRs, 3 tumor was a recurrence, and the rest occurred de novo. The most common cancers in women were breast cancers (17.8%), colon cancers (14.5%), lung cancers and post-transplant lymphoproliferative disorder (PTLD) (8.9% each). In males, the most common cancers were native kidney cancer (16.4%), lung cancer (15.7%) and prostate cancer (14%). During the study period, among KTRs who developed solid organ malignancy, NMSC was diagnosed in 7.3% of recipients. The average time of occurrence of malignant tumors was 84.5 months/7 years after kidney transplantation (KTx), and most cancers developed in the range of 1–5 years (33.6%) and 5–10 years (34.42%) after KTx. Nearly half (48.8%) of patients died due to cancer.ConclusionsSimilarly to the general population, the most common cancers among KTRs included breast and prostate cancer, as well as colorectal and lung cancer. Attention should be paid to the extremely frequent occurrence of native kidney and lymphatic system cancers in this group of KTRs. The frequent occurrence of cancer in KTRs requires systematic screening in this population.